The Bahamas. Significant Achievements 2023 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
It highlights the significant support provided by the Inter-American Institute for Cooperation on Agriculture (IICA) in The Bahamas in 2023. Key points include IICA's backing of initiatives to boost the economic development of tourism in The Bahamas by participating in various international and national tourism-related committees, such as the UN Tourism's "Best Tourism Villages" program. Additionally, IICA promotes the "Buy Fresh, Buy Local, Buy Bahamian" campaign to encourage support for local agriculture and producers, with further reinforcement through sponsorships at events like the International Food Festival and the West Indies Agricultural Economics Conference. IICA delivers logistical and technical assistance to the local community, supporting groups like The Bahamas Network of Rural Women Producers (BAHNROP) and the Agricultural Alliance of the Caribbean (AACARI). The institute also provides financial and logistical resources to enable representation at critical international meetings, including those of the Codex Alimentarius Commission and essential food safety gatherings. Furthermore, the document mentions IICA hosting GEF project sensitization workshops in four Family Islands to introduce farmers and stakeholders to new project outputs, successfully developing a GEF Inception Report for the government to address land degradation and climate risks. IICA's technical cooperation in The Bahamas includes presentations, workshops, and educational events to promote resilient agriculture and increase local food production.